Encyclopedia Brown gets his man - Sobol, Donald J., 1924-; Shortall, Leonard W. ([Camden, N.J.] Scholastic Book Services by arrangement with T. Nelson, 1967)
Ten brief cases in which the reader pits his wits against those of Encyclopedia Brown, an ingenious twelve-year-old detective.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
3.1
3-6
Keywords: Mystery and detective stories; Mystery and detective stories